2010
DOI: 10.1016/j.jjcc.2009.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to left atrial enlargement in adults with normal left ventricular systolic function

Abstract: Increased LV wall thickness and decreased hemoglobin concentration might contribute to LA enlargement in patients with normal LV systolic function irrespective of gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
5
15
0
1
Order By: Relevance
“…This is consistent with observation from human in that Japanese women display a smaller LV mass compared with age-matched Japanese men (Katayama et al , 2010). In a smaller-scale study performed in Nigerians, women display a trend but insignificant decrease in LV mass compared with age-matched men (Ogah and Bamgboye, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with observation from human in that Japanese women display a smaller LV mass compared with age-matched Japanese men (Katayama et al , 2010). In a smaller-scale study performed in Nigerians, women display a trend but insignificant decrease in LV mass compared with age-matched men (Ogah and Bamgboye, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…This subtle difference in the LV mass between men and women may be related to the apparent differences in ethnicity and blood pressure (Nigerian participants were hypertensive). Our study did not reveal any sex difference in fractional shortening, again similar that reported in the human setting (Katayama et al , 2010). .…”
Section: Discussionsupporting
confidence: 92%
“…PF volume is increased in obese patients and correlates with the presence [7,8] and incidence [9] of coronary atherosclerosis independent of other risk factors, indicating that PF may have paracrine or mechanical effects on the coronary circulation and myocardium. PF volume has also been reported to correlate with left atrial diameter, which is an indirect structural parameter of LVDD [10][11][12]. However, there is currently no report of a functional parameter of LVDD by tissue Doppler echocardiography that correlates with PF volume.…”
Section: Introductionmentioning
confidence: 99%
“…Neurological status on the first day by NIHSS turned out to be an independent risk factor for unfavorable prognosis (just like n e u r o l o g i a i n e u r o c h i r u r g i a p o l s k a 5 2 ( 2 0 1 8 ) 1 5 6 -1 6 1 reduced EF) and death (again CHA2DS2VASc ≥3 points). A neurological status estimation based on NIHSS, just like clinical profile evaluation by CHA2DS2VASc in this group of patients, is one of the key prognostic parameters for the functioning of post-stroke patients and for death [16,29,30]. Most probably, there are a few factors related to AF which modify the acute phase of stroke.…”
Section: Discussionmentioning
confidence: 98%